Afro-Cuban Costumbrismo : From Plantations to the Slums. - Ocasio, Rafael (Florida James Joyce series., 2012)
Costumbrismo, which refers to depictions of life in Latin America during the nineteenth century, introduced some of the earliest black themes in Cuban literature. Rafael Ocasio delves into this literature to offer up a new perspective on the development of Cuban identity, as influenced by black culture and religion, during the sugar cane boom. Comments about the slave trade and the treatment of slaves were often censored in Cuban publications; nevertheless white Costumbrista writers reported on a vast catalogue of stereotypes, religious beliefs, and musical folklore, and on rich African trad.